Introduction of a team-based care model in a general medical unit. Issue 1 (December 2016) - Hastings, Stephanie; Suter, Esther; Bloom, Judy; Sharma, Krishna
Abstract Background Alberta Health Services is a provincial health authority responsible for healthcare for more than four million people. The organization recognized a need to change its care delivery model to make care more patient- and family-centred and use its health human resources more effectively by enhancing collaborative practice. A new care model including changes to how providers deliver care and skill mix changes to support the new processes was piloted on a medical unit in a large urban acute care hospital Evidence-based care processes were introduced, including an initial patient assessment and orientation, comfort rounds, bedside shift reports, patient whiteboards, Name Occupation Duty, rapid rounds, and team huddles. Small teams of nurses cared for a portion of patients on the unit. The model was intended to enhance safety and quality of care by allowing providers to work to full scope in a collaborative practice environment. Methods We evaluated the new model approximately one year after implementation using interviews with staff (n  = 15), surveys of staff (n  = 25 at baseline and at the final evaluation) and patients (n  = 26 at baseline and 37 at the final evaluation), and administrative data pulled from organizational databases. Results Staff interviews revealed that overall, the new care processes and care teams worked quite well. Unit culture and collaboration were improved, as were role clarity, scope of practice, and patient care. Responses from staff surveys were also very positive, showing significant positive changes in most areas. Patient satisfaction surveys showed a few positive changes; scores overall were very high. Administrative data showed slight decreases in overall length of stay, 30-day readmissions, staff absenteeism, staff vacancies, and the overtime rate. We found no changes in unit length of stay, 30-day returns to emergency department, or nursing sensitive adverse events. Conclusions Conclusions from the evaluation were positive, providing initial support for the idea of the collaborative practice model vision for adult medical units across Alberta. There were also a few positive effects on patient care suggesting that models such as this one could improve the organization's ability to deliver sustainable, high-quality, patient- and family-centred care without compromising quality.